Optimization of PCR Annealing Temperature for Pir-A Gene Detection in Vibrio parahaemolyticus Source AHPND in Litopenaeus vannamei By MultiNA - Oktaviani Kumala Sari; Yuni Kilawati; Sri Andayani; Kurrotul Uyun; Aditya Ragil Suharto (Department of Aquaculture, 2026)
Acute Hepatopancreatic Necrosis Disease (AHPND) is a bacterial disease that causes high mortality rates and severe economic losses in Litopenaeus vannamei aquaculture. This disease is associated with pathogenic Vibrio parahaemolyticus strains carrying the PirA virulence gene. Therefore, early and accurate detection of AHPND is essential for effective disease management. Polymerase Chain Reaction (PCR) is widely used for molecular detection; however, its performance is greatly influenced by annealing temperature optimization. This study aimed to determine the optimal PCR annealing temperature for detecting the PirA gene in V. parahaemolyticus isolated from shrimp infected with AHPND using a microfluidic electrophoresis system (MultiNA). Conventional PCR was performed using annealing temperature gradients of 50°C, 55°C, 57°C, and 60°C. PCR products were analyzed using MultiNA to evaluate DNA band patterns, fragment size, concentration, and molarity. The results showed that the pirA gene was successfully amplified at all temperatures tested, producing DNA fragments measuring 134–136 bp. The highest amplification efficiency, specificity, and consistency were obtained at an annealing temperature of 57°C, as indicated by the most dominant DNA band and the highest concentration and molarity values. Lower annealing temperatures resulted in non-specific amplification, while higher temperatures reduced amplification stability. In conclusion, an annealing temperature of 57°C is optimal for PCR-based detection of the pirA gene in V. parahaemolyticus, and the use of the MultiNA system provides accurate and objective PCR product analysis for AHPND diagnostics.